The Influence of Selling Prices on Rice Farmers' Income in Tanjung Selamat Village, Percut Sei Tuan District, Deli Serdang Regency - Damai Yanti Br Sihite, Putri; Sihombing, Natalia ET; Simangunsong, Ridhon. Mb. (Manunggal Halim Jaya, 2024)
This research aims to find out how much the selling price influences the income level of rice farmers in Tanjung Selamat Village, Percut Sei Tuan District, Deli Serdang Regency. The type of research used is a quantitative approach method. The population in this research is rice farmers in Tanjung Selamat Village, Percut Sei Tuan District, Deli Serdang Regency. The samples in this research were 78 rice farmers. The type and technique of data collection used in this research is primary data using a questionnaire. The data analysis methods used are instrument tests, namely validity and reliability tests, Descriptive Statistical Analysis, Simple Regression Analysis, Hypothesis Testing, namely the t test (partial test) and the Coefficient of Determination (R2) test. The results of this research show that the selling price variable has a tcount value of 9.208 while the ttable is 1.991, indicating that the tcount > ttable value is significant at 0.000 because the significance is smaller than 0.05 (0.000<0.05) so it can be concluded that partially the Selling Price (x) significantly influences Income (Y). This is indicated by a tcount value of 9.208 ttable 1.991 and a significant value of 0.000<0.05. The Determination Coefficient (R2) was obtained at 0.527 so it can be seen that the ability of the Selling Price (X) variable to explain the Income (Y) variable is 0.527 or 52.7% and the remaining 47.3% is explained by other variables not included in the research model This. It is recommended that rice farmers pay more attention to determining selling prices. Because setting selling prices greatly affects farmers' income. Apart from paying attention to the selling price, farmers must also pay attention to all the costs incurred in maintaining rice.